Aplikasi Berbagai Jenis Pupuk Organik Cair dari Berbagai Jenis Pelarut Terhadap Pertumbuhan dan Produksi Rumput Gajah Mini (Pennisetum purpureum CV. Mott) - Maria Erviana Kusuma (Fakultas Peternakan Universitas Kristen Palangka Raya, 2021)
This study aims to know the effect of Liquid Organic Fertilizer from Various Types of Solvents To The Growth and Production of Mini Elephant Grass (Pennisetum purpureum CV. Mott) and to know the effect of Liquid Organic Fertilizer from Various Types of Solvents which gives the best results on The Growth and Production of Mini Elephant Grass (Pennisetum purpureum CV. Mott). This study was designed using a Completely Randomized Design (CRD) with a single treatment of Various Types of Solvents Liquid Organic Fertilizer. P1 = Liquid Organic Fertilizer from River Water, P2 Liquid Organic Fertilizer from Rainwater, P3 = Liquid Organic Fertilizer from Peat Water, P4 = Liquid Organic Fertilizer from soil water and P5 = Liquid Organic Fertilizer from Mineral Water. The results of this study are that the application of Liquid Organic Fertilizer (POC) from various types of solvents has no effect on the growth and production of Gajah Mini grass (Pennisetum purpureum CV. Mott). Keywords : Applications, liquid organic fertilizer, solvent.